Kinetics of Bacterial Reduction of Hematite by Acidithiobacillus ferrooxidans-r4A1FC2B3 - Tekin, Derya; Yoruk, Sedat; Kocadagistan, Engin (Asian Journal of Chemistry, 2013)
The kinetics of bacterial reduction of hematite has been studied by using r4A1FC2B3 strain of Acidithiobacillus ferrooxidans. Hematite is dissolved in acidic medium and with the Fe(II) ions it is oxidized to Fe(III). Then Fe(III) ions are reduced to Fe(II) ions again with the bacteria. For the experiments carried out to study the kinetics of bacterial reduction of hematite, the concentration values of Fe(III) samples taken during exponential phase, which took place after the 14th day were used. It was seen that bacterial reduction of hematite fits to the Monod kinetics.